Planejamento de sistema de contenção de cheias para a Rua Edmundo Hosfster em Francisco Beltrão - PR - Lombardo, Açucena (2021)
The unrestrained process of urbanization ends up always seeking areas with available natural resources, generating the occupation of areas not suitable for residential use, these areas being located in regions with larger riverbeds, which when heavy rains occur, this population ends up being significantly affected. The present work presents a proposal for a project for the implementation of a containment basin in order to store the excess volume of water from rainfall that causes damage to the population living in the area close to Edmundo Hosfster Street due to flooding. The methodology followed for the planning of the containment basin followed the application of the Rational Method to estimate the influent flow for the fully urbanized basin and the effluent flow that is limited to the drainage capacity of the existing pipeline in the study area. Thus, 3 application conditions were simulated according to the payback periods used. These corresponding to 25 years (Condition 1), 50 years (Condition 2) and 100 years (Condition 3), and after establishing the values, the precipitation intensities, the influent flow, the preliminary volume that should be calculated for each condition were calculated. stored. The geoprocessing was carried out using the Digital Elevation Model of the urban area of Francisco Beltrão and also an on-site visit to obtain the points referring to the piping responsible for local drainage. Contour curves were generated with an equidistance of 0.5 meters, so that the relationship between the area occupied by each level and the stored volume could be surveyed, so that through these values the appropriate levels of the dike could be established (dam) according to each proposed condition. Association between the quotas and the volume held by the dam to obtain the hydraulic load to which the pipeline is submitted, enabling the calculation of the effluent flow. In this way, it was possible to establish the delimitation of the containment basin at the location and height of the downstream dike for each condition.